Rapid rise in prevalence of knee replacements and decrease in revision burden over past 3 decades in Finland: a register-based analysis - Pamilo, Konsta J; Haapakoski, Jaason; Sokka-Isler, Tuulikki; Remes, Ville; Paloneva, Juha (Acta orthopaedica, 2022)
Background and purpose: The prevalence of knee joint replacements (KJR) has been less investigated in situations where the increase in incidence is known. This study investigated the annual and population-based prevalence of KJR and the relationship between the prevalence of KJRs and the incidence of revision surgery. Patients and methods: All KJRs performed between 1980 and 2020 were identified from the Finnish Arthroplasty Register (FAR). KJR revisions and removals were extracted from the FAR and hospital discharge registers and patient deaths from Finnish Digital and Population Data Services Agency. We analyzed the annual prevalence by dividing the number of KJR survivors by the population aged 40 or older. The revision burden factor (RBF) was determined by dividing the annual number of revisions by the number of primaryand revision KJRs in the population. Proportions of bilateral implants and patients with older KJRs performed 10 or more years earlier were identified. Results: KJR prevalence in Finland increased by 298% between 2000 and 2020, reaching 4.0% in 2020. The proportion of patients with bilateral KJRs and those with older KJRs had increased to 37% and 34%, respectively, by 2020. The annual RBF decreased statistically significantly from 1.9% to 0.7% between 1996 and 2020 (proportion ratio, PR 0.37 [95% CI 0.33–0.42]) and was higher among males (PR1.23 [CI 1.20–1.26]). Interpretation: Although the recent rapid increase in KJRs is abating and the RBF is diminishing, it is important to take the continuing increase in the prevalence of KJRs into account when assessing hospitals’ future resources.